1997
DOI: 10.1210/mend.11.8.9960
|View full text |Cite
|
Sign up to set email alerts
|

ActivationIn Vitroof Somatostatin Receptor Subtypes 2, 3, or 4 Stimulates Protein Tyrosine Phosphatase Activity in Membranes from Transfected Ras-Transformed NIH 3T3 Cells: Coexpression with Catalytically Inactive SHP-2 Blocks Responsiveness

Abstract: Somatostatin receptors (sstr) subtypes 1-5 were transiently expressed in NIH 3T3 cells stably transformed with Ha-Ras(G12V) to assess the ability of each receptor to stimulate protein tyrosine phosphatase (PTPase) activity in vitro. Treatment of membranes from sstr2-, sstr3-, or sstr4-expressing cells with somatostatin-14 plus guanyl-5'-yl imidodiphosphate (GMPPNP) increased PTPase activity, and this stimulation was pertussis toxin-sensitive. Somatostatin alone, GMPPNP alone, or somatostatin plus GDP were inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In primary cultures of GH-secreting and non-functioning pituitary adenomas, LAN induces anti-proliferative activity through the induction of a PTP activity [49,50], while OCT triggers SHP1 activity in GH4C1 rat pituitary adenoma cell line [51]. SHP1 and/or SHP2 activities are also induced by SST 1 [52,53], SST 2 [54,55], SST 3 [55], and SST 4 [55,56], while PTPη is activated by SST 1 , SST 2 , and SST 5 , as shown in cells endogenously expressing the different SST subtypes [41]. The molecular mechanisms connecting SSTs and PTPs have not been completely clarified, but likely are not directly induced by G protein activation and involve the modulation of different intracellular transducers [47].…”
Section: Introductionmentioning
confidence: 99%
“…In primary cultures of GH-secreting and non-functioning pituitary adenomas, LAN induces anti-proliferative activity through the induction of a PTP activity [49,50], while OCT triggers SHP1 activity in GH4C1 rat pituitary adenoma cell line [51]. SHP1 and/or SHP2 activities are also induced by SST 1 [52,53], SST 2 [54,55], SST 3 [55], and SST 4 [55,56], while PTPη is activated by SST 1 , SST 2 , and SST 5 , as shown in cells endogenously expressing the different SST subtypes [41]. The molecular mechanisms connecting SSTs and PTPs have not been completely clarified, but likely are not directly induced by G protein activation and involve the modulation of different intracellular transducers [47].…”
Section: Introductionmentioning
confidence: 99%
“…The actions of these two agonists are mediated by at least five different somatostatin receptor subtypes (SSTR1–SSTR5), which are all coupled to G‐proteins of the pertussis toxin sensitive G i /G o class. In heterologous expression systems it has been shown that, dependent on the cellular environment, these receptors can be coupled to the inhibition of adenylyl cyclase [2]and voltage‐dependent calcium channels [3], the activation of tyrosine phosphatases [4], phospholipase C [5]and of a phospholipase A 2 [6]. In addition, it has frequently been observed in neuronal and neuroendocrine cells that SST leads to the hyperpolarization of the cell membrane by activation of G‐protein gated inwardly rectifying potassium (GIRK) channels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Other factors associated with the direct effect of SSTR-induced antiproliferation are protein tyrosine phosphatases (PTPases) [28]. Previous studies using Ras-transformed NIH 3T3 cells have described how the PTPases in these cells are activated by SSTR2, SSTR3 and SSTR4 [29]. Florio et al demonstrated SSTR1-induced cell growth inhibition in transfected CHO-K1 cells by activating SHP-2, which resulted in the MAPK pathway's stimulation [21].…”
Section: Somatostatin Receptors: Signaling Pathways and Cell Prolifer...mentioning
confidence: 99%